Порівняльна паліноморфологічна характеристика видів з різними типами екологічних стратегій - Kosakivska, I.V.; Tsymbalyuk, Т.I.; Tsymbalyuk, Z.M. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2011)
Pollen grains of 5 species with different types of ecological strategies were studied using light and scanning electron microscopy. Pollen grains of Rumex tianschanicus and Brassica campestris were analyzed by these methods at first time. Pollen grains of studied species characterized by similar size and form but have different type of apertures and sculpture surface of exine. The palynomorphological peculiarities of species were described. The correlation between mains characteristics of pollen grains and type of ecological strategy of the species was revealed.